2007
DOI: 10.1080/10837450701366952
|View full text |Cite
|
Sign up to set email alerts
|

Use of Compaction Energetics for Understanding Particle Deformation Mechanism

Abstract: A primary goal of the current work was to examine the potential use of compaction energetics as a tool to predict particle deformation mechanism. Three deformation models, namely, those developed by Heckel, Walker, and Gurnham, were first used to evaluate the deformation mechanisms of 11 commonly used excipients. To complement the information gained from the deformation models, the mechanical energy used in tablet formation was then examined. It has been found that the sum of the work in the compression and de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(13 citation statements)
references
References 24 publications
0
13
0
Order By: Relevance
“…All samples were compressed using an approximate load of 22 kN, which corresponds to an applied pressure of 28 MPa. Although solid fraction is an important property of compacted powders, especially for strength measurements, the response of all materials to the same applied load has been found to be a reliable means of comparing energy values 7, 16, 17. The maximum load was maintained for 5 s before decompression.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…All samples were compressed using an approximate load of 22 kN, which corresponds to an applied pressure of 28 MPa. Although solid fraction is an important property of compacted powders, especially for strength measurements, the response of all materials to the same applied load has been found to be a reliable means of comparing energy values 7, 16, 17. The maximum load was maintained for 5 s before decompression.…”
Section: Methodsmentioning
confidence: 99%
“…Many varied approaches have been proposed to characterize the compaction behavior of the diverse materials that are used to make pharmaceutical tablets, but no single approach is recognized as a universal solution 3, 5–9. Several studies have attempted to use thermodynamic measurements as a means to study compaction at a fundamental level 10–13.…”
Section: Introductionmentioning
confidence: 99%
“…The first three materials are known to deform predominantly by plastic behavior under pressure (8). However, the last three materials are known to deform predominantly by brittle fracture under pressure (8)(9)(10)(11)(12). In-die, Heckel analysis (2) was performed on all powders.…”
Section: Methodsmentioning
confidence: 99%
“…Some models address the mechanical energy consumed during compaction of a particle bed, which can be derived from loadedisplacement profiles collected during compression. Aburub, Mishra, and Buckner (2007) found that the sum of the works in the compression and decompression phases (in a hysteresis test on the particle bed) is a good indicator of a material susceptibility to compression. To some extent, higher energy inputs may be associated with a more plastic deformation (Aburub et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Aburub, Mishra, and Buckner (2007) found that the sum of the works in the compression and decompression phases (in a hysteresis test on the particle bed) is a good indicator of a material susceptibility to compression. To some extent, higher energy inputs may be associated with a more plastic deformation (Aburub et al, 2007). Mechanical response to loading of a particle bed system can be broadly modified changing processing conditions, addition of water or other agents enhancing bonding and lowering friction.…”
Section: Introductionmentioning
confidence: 99%